Fortæller og tema. Pontoppidans Mimoser læst igen - Holmgaard, Jørgen (K&K - Kultur og Klasse, 2006)
Narration and thematics. Pontoppidan’s Mimoser read once again In Danish literary criticism Pontoppidan’s short novel Mimoser (1886) has maintained a reputation for being an enigmatic piece of fiction. What is it really about, and what is its point in the end? This paper approaches the text by close-reading the oblique, changing relationships between the implied narrator, the characters he presents, and the grim story he tells about how their life projects are ruined. In contrast to the elusive enunciation of the text, its thematic structure is very stable, however. The ‘vertical’ relationships between parents and their children persistently dominate the grown-up children’s wishes and futile attempts to form permanent ‘horizontal’ matrimonial relationships. Especially the dominance of the mother in relation to the son is decisive for the outcome of these conflicts. Eventually, the paper sketches what happens to the way Pontoppidan narrates in his long, monumental novels later on.